Computation of the 1‐dB compression point in radio frequency amplifier circuits using moments analysis - Tannir, Dani A. (2015)
Nonlinear distortion analysis is one of the most computationally challenging aspects in the simulation of radio frequency circuits. Recently, an efficient moments‐based approach to determine the third‐order intercept point from the general harmonic balance equations, without the need to perform a harmonic balance simulation, was presented. In this article, the efficient computation of another important performance figure of merit, that of the 1‐dB compression point, using moments analysis is presented. In addition, the computations of the second‐ and fifth‐order intercept points are also presented. As a result, moments analysis becomes a comprehensive approach for quantifying nonlinear distortion using several key distortion figures of merit with a significant speed‐up over traditional harmonic balance methods. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:10–20, 2015.